ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS DALAM MENDUKUNG PEMBIAYAAN PADA PT BANK DANAMON INDONESIA, TBK. - Lia Dahlia Iryani; Herlina Herlina (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2015)
The performance assessment of the financial aspects of the company more frequently using financial ratio analysis techniques. This analysis requires the financial statements at least the last two years. With the financial ratio analysis will be able to determine the level of liquidity, solvency, and profitability. A research technique that used is quantitative analysis (nonstatistik). From the research result showed that the ratio of liquidity, solvency, and profitability tends to increase and financing of PT Bank Danamon Indonesia, Tbk was in a healthy state, based on the results of tests performed that financing in PT Bank Danamon Indonesia, Tbk in 2011 increased by 777 962. This is due to an increase in the level of solvency. Increased financing occurs due to the condition of PT Bank Danamon Indonesia, Tbk. in a liquid state when viewed from the level of liquidity.Keywords: Liquidity Ratios, Solvency Ratios, Profitability Ratios, and Financing